O conceito de estilo em Lacan - Franco, Bruno Fiuza (2017)
This work seeks to ascertain a possible conceptualization of style in the Lacanian psychoanalytic work. This term, present at various moments in his work, does not find a consistent theoretical limitation and its meaning can only be abstracted from its occurrences. This study was based on the Lacanian claim that style is the object, or at another time, it is man, but only if we define what man is. These phrases drive Lacan away from the stylistic pretension of investigating the ways in which discourse manifests itself as a subjective impression in the work. In Lacanian psychoanalysis style is linked to the object, or rather, the dimension of have been object to which the subject has been subjected in its formation. The re-updating of this state, which has been repressed, allows the subject, in front of the real, to create a style. This time we investigated how this thesis reflects on Lacan's own style and his attempt to transmit psychoanalysis insofar as its object is not of the order of the objectifiable.